Drug Repurposing: In vitro and in vivo Antimicrobial and Antibiofilm Effects of Bithionol Against Enterococcus faecalis and Enterococcus faecium - She, Pengfei; Wang, Yangxia; Li, Yingjia; Zhou, Linying; Li, Shijia; Zeng, Xianghai; Liu, Yaqian; Xu, Lanlan; Wu, Yong (Frontiers in Microbiology, 2021)
Widespread antibiotic resistance has been reported in enterococcal pathogens that cause life-threatening infections. Enterococci species rapidly acquire resistance and the pace of new antibiotic development is slow. Drug repurposing is a promising approach in solving this problem. Bithionol (BT) is a clinically approved anthelminthic drug. In this study, we found that BT showed significant antimicrobial and antibiofilm effects against Enterococcus faecalis and vancomycin-resistant Entercococcus faecium in vitro, in a dose-dependent manner, by disrupting the integrity of the bacterial cell membranes. Moreover, BT effectively reduced the bacterial load in mouse organs when combined with conventional antibiotics in a peritonitis infection model. Thus, BT has shown potential as a therapeutic agent against E. faecalis- and vancomycin-resistant E. faecium-related infections.